Assessment and management of bone health in women with oestrogen receptor‐positive breast cancer receiving endocrine therapy: Position statement of the Endocrine Society of Australia, the Australian and New Zealand Bone & Mineral Society, the Australasian Menopause Society and the Clinical Oncology Society of Australia. (14th June 2018) - Grossmann, Mathis; Ramchand, Sabashini K.; Milat, Frances; Vincent, Amanda; Lim, Elgene; Kotowicz, Mark A.; Hicks, Jill; Teede, Helena
Summary: To formulate clinical consensus recommendations on bone health assessment and management of women with oestrogen receptor‐positive early breast cancer receiving endocrine therapy, representatives appointed by relevant Australian Medical Societies used a systematic approach for adaptation of guidelines (ADAPTE) to derive an evidence‐informed position statement addressing 5 key questions. Women receiving adjuvant aromatase inhibitors and the subset of premenopausal woman treated with tamoxifen have accelerated bone loss and increased fracture risk. Both bisphosphonates and denosumab prevent bone loss; additionally, denosumab has proven antifracture benefit. Women considering endocrine therapy need fracture risk assessment, including clinical risk factors, biochemistry and bone mineral density (BMD) measurement, with monitoring based on risk factors. Weight‐bearing exercise, vitamin D and calcium sufficiency are recommended routinely. Antiresorptive treatment should be considered in women with prevalent or incident clinical or morphometric fractures, a T ‐score (or Z ‐scores in women <50 years) of <−2.0 at any site, or if annual bone loss is ≥5%, considering baseline BMD and other fracture risk factors. Duration of antiresorptive treatment can be individualized based on absolute fracture risk. Relative to their skeletal benefits, risks of adverse events with antiresorptive treatments are low. Skeletal health should be considered in the decision‐making process regarding choice and duration of endocrine therapy. Before and during endocrine therapy, skeletal health should be assessed regularly, optimized by nonpharmacological intervention and where indicated antiresorptive treatment, in an individualized, multidisciplinary approach. Clinical trials are needed to better delineate long‐term fracture risks of adjuvant endocrine therapy and to determine the efficacy of interventions designed to minimize these risks.